Real Property Tax Collection in Sta. Josefa, Agusan Del Sur, Philippines: An Exploratory Research Analysis - Marzon Q. Fuentes; Aristeo C. Salapa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research study is conceptualized to provide information on the real property tax collection in Sta. Josefa, Agusan del Sur. This employs a documentary-descriptive-research method using secondary sources of information generated from archives, and documents such as the Certified List of Real Property Tax Delinquencies, and the Electronic New Government Accounting System. Moreover, JASP is utilized to illustrate the tax collection delinquency on real property with and without government intervention. The findings of this study include that there is a compelling linkage between government intervention on tax collection of real property. It describes the importance of the interventions as a way of improving collection efficiency and reducing tax delinquency.